Active learning: The importance of developing a comprehensive measure. (November 2015) - Carr, Rodney; Palmer, Stuart; Hagel, Pauline
This article reports on an investigation into the validity of a widely used scale for measuring the extent to which higher education students employ active learning strategies. The scale is the active learning scale in the Australasian Survey of Student Engagement. This scale is based on the Active and Collaborative Learning scale of the National Survey of Student Engagement. The particular focus of the study was to investigate effects resulting from the addition of a small number of items to the active learning scale designed to capture some highly engaging, mostly online, activities. The items were developed in response to concerns that students studying in distance mode often report lower average scores on active learning scales than their on-campus counterparts. The additional items relate to activities such as working online with other students and faculty. The findings show that average scores on the Australasian Survey of Student Engagement/National Survey of Student Engagement scale increase significantly when the new items are included and that some differences between on-campus and distance education students narrow significantly. These findings have implications for the development of more robust and comprehensive instruments to measure active learning.